Correlation of AlGaN/GaN high-electron-mobility transistors electroluminescence characteristics with current collapse. (23rd January 2018) - Ohi, Shintaro; Yamazaki, Taisei; Asubar, Joel T.; Tokuda, Hirokuni; Kuzuhara, Masaaki
Abstract: We report on the correlation between the electroluminescence and current collapse of AlGaN/GaN high-electron-mobility transistors (HEMTs). Standard passivated devices suffering from severe current collapse exhibited high-intensity whitish electroluminescence confined near the drain contact. In contrast, devices with reduced current collapse resulting from oxygen plasma treatment or GaN capping showed low-intensity reddish emission across the entire gate–drain access region. A qualitative explanation of this observed correlation between the current collapse and electroluminescence is presented. Our results demonstrate that electroluminescence analysis is a powerful tool not only for identifying high-field regions but also for assessing the degree of current collapse in AlGaN/GaN HEMTs.